2018
DOI: 10.1002/smi.2831
|View full text |Cite
|
Sign up to set email alerts
|

How to benefit from weekend physical activities: Moderating roles of psychological recovery experiences and sleep

Abstract: This study examines the short-term recovery benefits of weekend physical activity on reduced negative affective state (NA) on Monday morning, using a weekly diary method from 70 employees across four weekends (repeated pre- and post-weekend measures). The first hypothesis tests the within-person relationship between weekend physical activity and post-weekend NA. The results of multilevel path analysis show that the main effect of weekend physical activity on reduced Monday NA is not significant. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Second, our study found the key mediating mechanism to explain how weekend activities promoted employees' psychological well-being. Several studies have examined how weekend or leisure activities influenced employees' attitude toward their job and life such as job stress, life satisfaction, and recovery experiences [17,22,33,47,48]; however, the relationships among weekend activities, job stress, and psychological well-being have been rarely investigated. In particular, by identifying the substantial mediating role of job stress, this study provides useful insights to understand the key mechanism of how weekend activities facilitate psychological well-being of employees.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our study found the key mediating mechanism to explain how weekend activities promoted employees' psychological well-being. Several studies have examined how weekend or leisure activities influenced employees' attitude toward their job and life such as job stress, life satisfaction, and recovery experiences [17,22,33,47,48]; however, the relationships among weekend activities, job stress, and psychological well-being have been rarely investigated. In particular, by identifying the substantial mediating role of job stress, this study provides useful insights to understand the key mechanism of how weekend activities facilitate psychological well-being of employees.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…However, previous studies on job stress and psychological well-being have addressed the issue from an organizational perspective [19][20][21]. Recently, it was reported that employees' weekend activities help recover the energy resource they expend at work [22,23]. The activities were also found to enhance their feeling of personal well-being by improving their mental and physical states and were thus seen as being positively associated with regular work activities [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[4], physical activities for children and teenager are correlated with a lot of health benefits, including obesity avoidance, density improvement of bone mineral, decreasing risk factors of metabolic and cardiovascular diseases and improve mental health. This was confirmed by Cho & Park in 2018 [5] who found that physical activities were related to long terms health benefit such as a reduction in heart and respiratory disease and other cause of death. According to Kudlacek et al in 2016 [6], teenagers should be encouraged to counterbalance their school activity burden with physical activities at the weekend.…”
Section: Introductionmentioning
confidence: 68%
“…According to Habib [1] in 2010, people might conduct various activities during weekend, e.g. : (1) basic needs, such as take a nap, dealing with laundry, dress up, tidying up the house, having lunch, having dinner and breakfast, (2) working/ studying including telework, voluntary work, training, etc., (3) household duties such as cleaning, childcare, animal-care, etc., (4) deliver/ pick-up passengers, meals, snacks, video rental, sending mail, etc., (5) shopping activities such as buying groceries, personal needs, etc., (6) service activities such as health-care/ hospital, personal care, banking, religious activities, vehicle-care, etc., (7) recreational and leisure activities, (8) social activities including visiting/ treating guests in a club, social event planning, lengthy telephone call, etc., and (9) other activities.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise, which refers to a subset of physical activity that is planned, structured, and repetitive and has a final or an intermediate objective to improve or maintain physical fitness (Caspersen et al, 1985), has gained attention as a promising intervention to reduce fatigue (De Vries et al, 2017). The relatively few intervention studies that have so far been conducted mostly show that exercise works to reduce the main component of burnout, fatigue (Brenninkmeijer & Van Yperen, 2003;Naczenski et al, 2017;Ochentel et al, 2018;De Vries et al, 2017).…”
Section: Introductionmentioning
confidence: 99%